2006
DOI: 10.1002/cyto.b.20105
|View full text |Cite
|
Sign up to set email alerts
|

Remission induction chemotherapy induces in vivo caspase‐dependent apoptosis in bone marrow acute myeloid leukemia blast cells and spares lymphocytes

Abstract: Background: The goal of new therapeutic strategies is to adapt the treatment of acute myeloid leukemia (AML) patients to the prognostic and/or to the hematological response.Methods: We analyzed in vivo apoptosis induction in blast cells and in lymphocytes of AML patients receiving remission induction treatment.Results: We show, on 12 peripheral blood samples, that the increase of peripheral apoptotic blast cells cannot be considered as the earliest marker of the treatment efficiency, because the significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…One study of adult AML patients suggested that cytarabine and daunorubicin therapy specifically depleted blast cells but left the bone marrow lymphocytes intact 36 . Therefore, this study provides an important perspective on the immunologic effects of AML chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…One study of adult AML patients suggested that cytarabine and daunorubicin therapy specifically depleted blast cells but left the bone marrow lymphocytes intact 36 . Therefore, this study provides an important perspective on the immunologic effects of AML chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…On leukemia samples, blast cells and lymphocytes were identified by flow cytometry on the basis of their scatter properties and CD45 (PC5-conjugated anti-CD45; Beckman-Coulter, Margency, France) expression [23,24]. On normal bone marrow mononuclear cells, progenitor cells were identified on the basis of CD34 expression and scatter properties.…”
Section: Analysis Of Apoptosis By Flow Cytometrymentioning
confidence: 99%
“…He underlined the importance of cardiolipin (CL) as a key point in apoptosis pathway (88)(89)(90)(91)(92). CL is a mitochondria-specific phospholipid intimately involved in several apoptotic steps.…”
Section: Cell Death Drug Testing and Toxicologymentioning
confidence: 99%